2014
DOI: 10.1177/0194599814556239
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Thickened Liquids for Eliminating Aspiration in Head and Neck Cancer

Abstract: Objective To appraise the current videofluoroscopic evidence on the reduction of aspiration using thickened liquids in the head and neck cancer population. Data Sources Search terms relating to deglutition or dysphagia or swallow and neoplasms and oncology or head and neck cancer and viscosity or texture and apira or residu* were combined with honey or nectar, xerostomia, respiratory aspiration using Boolean operators. Review Methods A multi-engine literature search identified 337 non-duplicate articles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
(179 reference statements)
0
23
1
Order By: Relevance
“…Little prior data exist to demonstrate the predictive power of VFSS to alter clinical course . Current recommendations for dietary alteration following VFSS include various changes in dietary bolus viscosity to thickened liquids, mechanical consistencies, or full regular diet based on findings on oropharyngeal swallowing evaluation, but data supporting this practice are limited . Studies have also evaluated the ability of the PAS score to predict the ability of the patient to tolerate specific types of diet, but again these data are limited in scope .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Little prior data exist to demonstrate the predictive power of VFSS to alter clinical course . Current recommendations for dietary alteration following VFSS include various changes in dietary bolus viscosity to thickened liquids, mechanical consistencies, or full regular diet based on findings on oropharyngeal swallowing evaluation, but data supporting this practice are limited . Studies have also evaluated the ability of the PAS score to predict the ability of the patient to tolerate specific types of diet, but again these data are limited in scope .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the amount of swallowing therapy that is necessary to produce sufficient swallowing improvement to reduce pneumonia and mortality . A recent systematic review has shown that thickened liquids do seem to reduce risk of penetration and aspiration, but are also associated with higher pyriform residuals . Food hardness, cohesiveness (scatter potential), and viscosity are also highly associated with ease of transit through the hypopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the patients with head and neck cancers, evidences with thickened liquids are extremely limited [11]. Additionally, not thicken liquid but puree like Nectar was proved to be able to swallow ISSN: 2469-4185 without aspiration [12].…”
Section: Introductionmentioning
confidence: 99%